PENGARUH LIVE STREAMING DAN FLASH SALE TERHADAP IMPULSE BUYING PADA APLIKASI TIKTOK (STUDI KASUS BRAND SKINCARE THE ORIGINOTE) - Diah Pitaloka; Bambang Somantri (PT Naureen Digital Education, 2026)
This study aims to analyze the influence of Live Streaming and Flash Sale on the Impulse Buying behavior of The Originote skincare products on the TikTok platform. Along with the rapid growth of social commerce, interactive marketing strategies and time-based promotions have become crucial factors in triggering spontaneous purchasing decisions. The research method used is descriptive quantitative with multiple linear regression analysis techniques. Data were collected through questionnaires from 100 respondents who are TikTok users and consumers of The Originote in the Sukabumi area. The results of the partial test (t-test) show that Live Streaming has a very dominant and significant influence on Impulse Buying. Similarly, Flash Sale is proven to have a significant effect on impulsive purchasing. Simultaneously (F-test), both variables together have a significant effect on the dependent variable. These findings confirm that the synergy between direct visual interaction and the urgency of limited promotion is an effective strategy in driving impulsive shopping behavior on social media.